"Determinants of access to microcredit in Ijebu - ode local government area of Ogun state, nigeria " (2006)
Microcredit is an important input for enhanced productivity, employment and income generation among small and medium scale enterprises. Using stratified random sampling procedure; data were collected from 140 respondents in ljebu-Ode Local Government Area of Ogun state on the determinants of access to microcredit. The data were analysed with the aid of logistic regression analysis. The study reveals that being a male, having higher level of education, owning assets as well as generating income enhanced the log-likelihood of accessing credit. Thus, suggesting that these variables are key in improving access to microcredit in the area.